PENGARUH LINGKUNGAN KERJA TOXIC DAN KECERDASAN EMOSIONAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PDAM TIRTA HIDAYAH KOTA BENGKULU - Dimas Permana; Ratnawili Ratnawili (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
In a toxic work environment, employees' emotional intelligence is also an important factor in determining their ability to deal with the pressures of a non-conducive work environment. Emotional intelligence, which includes the ability to recognize, understand, and manage one's own and others' emotions, enables employees to remain productive despite challenging working conditions. This study aims to determine the effect of toxic work environment and emotional intelligence on employee productivity of PDAM Tirta Hidayah Bengkulu City. The type of research used is quantitative with descriptive methods. Data collection techniques are observation, interviews, and questionnaires. The number of samples used in this study amounted to 140 employees from a total population of 215 employees. The conclusions of this research analysis are 1). Toxic work environment has a significant negative effect on employee productivity at PDAM Tirta Hidayah Bengkulu. 2). Emotional intelligence has a significant effect on employee productivitya at PDAM Tirta Hidayah Bengkulu. 3). Toxic work environment and emotional intelligence have a significant effect on employee work productivity at  PDAM Tirta Hidayah Bengkulu. Keywords: Toxic Work Environment, Emotional Intelligence, Work Productivity.